Tunable nonlinear optical responses and carrier dynamics of two-dimensional antimonene nanosheets. Issue 10 (28th August 2020) - Zhang, Lei; Fahad, Shah; Wu, Hao-Ran; Dong, Tao-Tao; Chen, Zi-Zhen; Zhang, Ze-Qi; Liu, Rui-Tong; Zhai, Xin-Ping; Li, Xiang-Yang; Fei, Xian; Song, Qi-Wei; Wang, Zhe-Ji; et al.
Abstract : We developed a size-controlled intercalation method to prepare Sb nanosheets. A distinct size-dependent nonlinear optical response, unveiling the strong influence of the scale of the Sb nanosheets on the carrier dynamics was observed. Abstract : Sb nanosheets, also known as antimonene, have received ever-growing consideration as a promising new type of two-dimensional (2D) material due to their many attractive properties. However, how their nonlinear optical (NLO) properties are affected by their nanosheet structure and measurement conditions remains unclear. Herein, we report a successful size-selective production method for Sb nanosheets, which is based on a combination of lithium ion intercalation, solvent exfoliation and size selection centrifugation. This high-yield and size-selective preparation method enables fundamental investigation on the relation of the intrinsic optical properties of Sb nanosheets. Nanosecond Z -scan measurements revealed a unique size-dependent broadband NLO response. When the average size is reduced from 3 micrometers to 50 nanometers, the Sb nanosheets exhibit a clear transition from saturable absorption to reversed saturable absorption. Ultrafast transient absorption spectroscopic investigation indicated that exciton cooling is significantly faster in a small nanosheet than in large ones, revealing that the different exciton relaxation dynamic plays key roles in the distinct size-tunable nonlinear optical response. This work paves new ways towards the mass production and practical application of antimonene.